Varicose Eczema: Current State of The Problem (Texas Journal of Medical Science, 2024)
Varicose eczema, being a common dermatological manifestation of chronic venous diseases, nevertheless remains an insufficiently studied problem. Without being a dangerous disease, varicose eczema significantly reduces the quality of life of patients. The term “varicose eczema,” although it has become commonly used, is ambiguous. The problem of varicose eczema is primarily organizational: effective diagnosis and treatment requires interaction between surgeons and dermatologists. To date, there are no uniform approaches to diagnosing skin lesions in chronic venous insufficiency